-2y + 5z = -3
y = -5x - 4z - 5
x = 4z + 4
-2(-5(4z + 4) - 4z - 5) + 5z = -3
-2(-20z - 20 - 4z - 5) + 5z = -3
-2(-20z - 4z - 20 - 5) + 5z = -3
-2(-24z - 25) = -3
48z + 50 = -3
<u> - 50 - 50</u>
<u>48z</u> = <u>-53</u>
48 48
z = -1⁵/₄₈
x = 4(-1⁵/₄₈) + 4
x = -4⁵/₁₂ + 4
x = ⁵/₁₂
y = -5(⁵/₁₂) - 4(-1⁵/₄₈) - 5
y = -2¹/₂ + 4⁵/₁₂ - 5
y = 1¹¹/₁₂ - 5
y = -3¹/₂
(x, y, z) = (⁵/₁₂, -3¹/₂, -1⁵/₄₈)
Answer:
368 in^2
Step-by-step explanation:
To find the entire surface area, do the following:
Find the area of the base and then multiply it by 2:
(6 in)(5 in)(2) = 60 in^2
Find the area of one side and then mult. it by 2: then find the area of the other side and mult. that by 2 also. Add together these 3 results:
(6 in)(14 in)(2) + (5 in)(14 in)(2) + 60 in^2 = 368 in^2